Anticoagulation with warfarin and rivaroxaban ameliorates experimental autoimmune encephalomyelitis - Leonie Stolz; Amin Derouiche; Kavi Devraj; Frank Weber; Robert Brunkhorst; Christian Foerch (Journal of Neuroinflammation, 2017)
Abstract Background In multiple sclerosis, coagulation factors have been shown to modulate inflammation. In this translational study, we investigated whether long-term anticoagulation with warfarin or rivaroxaban has beneficial effects on the course of autoimmune experimental encephalomyelitis (EAE). Methods Female SJL/J mice treated with anticoagulants namely warfarin or rivaroxaban were immunized with PLP139–151. Stable anticoagulation was maintained throughout the entire experiment. Mice without anticoagulation treated with the vehicle only were used as controls. The neurological deficit was recorded during the course of EAE, and histopathological analyses of inflammatory lesions were performed. Results In preventive settings, both treatment with warfarin and rivaroxaban reduced the maximum EAE score as compared to the control group and led to a reduction of inflammatory lesions in the spinal cord. In contrast, therapeutic treatment with warfarin had no beneficial effects on the clinical course of EAE. Signs of intraparenchymal hemorrhage at the site of the inflammatory lesions were not observed. Conclusion We developed long-term anticoagulation models that allowed exploring the course of EAE under warfarin and rivaroxaban treatment. We found a mild preventive effect of both warfarin and rivaroxaban on neurological deficits and local inflammation, indicating a modulation of the disease induction by anticoagulation.